2000
DOI: 10.1046/j.1440-1754.2000.00544.x
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding failure in a longitudinal post‐partum maternal nutrition study in Hong Kong

Abstract: These results highlight difficulties in sustaining breastfeeding, either exclusive or partial, in Hong Kong Chinese women. Despite being recruited on the basis of intending to exclusively breastfeed for 3 months, less than half these mothers were still breastfeeding and only approximately one-third were exclusively or predominantly breastfeeding at 3 months. More needs to be done within the hospital environment to initiate breastfeeding immediately after birth and to avoid giving unnecessary supplements and mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 13 publications
5
45
0
5
Order By: Relevance
“…However, due to the low rate of exclusive breastfeeding rate in Hong Kong (Chan et al, 2000b) and the long-term follow-up, the present study was limited by small sample size. Other similar studies have also been limited by small sample sizes, with number of lactating subjects ranging from 9 to 26 (Hayslip et al, 1989;Cross et al, 1995;Krebs et al, 1997;Ritchie et al, 1998).…”
Section: Discussionmentioning
confidence: 93%
“…However, due to the low rate of exclusive breastfeeding rate in Hong Kong (Chan et al, 2000b) and the long-term follow-up, the present study was limited by small sample size. Other similar studies have also been limited by small sample sizes, with number of lactating subjects ranging from 9 to 26 (Hayslip et al, 1989;Cross et al, 1995;Krebs et al, 1997;Ritchie et al, 1998).…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, another study conducted in the year 2000 by the Hong Kong Department of Health found that only about 10 percent of women practised exclusive breastfeeding as recommended by WHO for the first 6 months of baby's life [16,17]. Found average level of breastfeeding initiation immediately after child birth to be 45 percent and within two hours after birth to be 29 percent among breastfeeding mothers in Southwest Nigeria (Yorubas).…”
Section: Introductionmentioning
confidence: 99%
“…1 Absence of or delay in the management of breastfeeding problems that arise after hospital discharge can result in discontinuation of exclusive breastfeeding as well as an increase in maternal and infant complications. [2][3][4][5] Improving access to quality medical care for breastfeeding mothers involves designing innovative models of healthcare delivery, which may include specialized breastfeeding medicine consultative services. 6,7 Models for providing professional medical services for outpatient breastfeeding support have been described in the literature in several countries, including Canada, Hungary, India, and Uganda.…”
Section: Introductionmentioning
confidence: 99%